2019
DOI: 10.31580/pjmls.v2i2.966
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Study on Pulmonary Tuberculosis (PTB) Predominance in Quetta.

Abstract: The study was conducted in the TB Sanatorium Quetta. A total 130 samples were collected from patient. While 43.75% and 56.25% tuberculosis prevalence were found both in male and female respectively with age group 28-54 years having the highest prevalence of tuberculosis. There was no difference between age groups and sex with pulmonary tuberculosis positive Subjects. Tuberculosis (TB) is a respiratory compelling contagious infection made by a germ or bacillus (Mycobacterium tuberculosis) affecting generally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…20 Pakistan, being a developing nation, is fighting against malnutrition which is a complex, multisectoral issue and has a bidirectional relationship with tuberculosis. 21,22 Khalid et al reported that TB patients in Pakistan were twice as likely to be malnourished than the healthy group. 23 TB group patients of the current study belonged to low socio-economic 3: Perception about TB treatment status and therefore might be malnourished as well as, we did not evaluate the physical status of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…20 Pakistan, being a developing nation, is fighting against malnutrition which is a complex, multisectoral issue and has a bidirectional relationship with tuberculosis. 21,22 Khalid et al reported that TB patients in Pakistan were twice as likely to be malnourished than the healthy group. 23 TB group patients of the current study belonged to low socio-economic 3: Perception about TB treatment status and therefore might be malnourished as well as, we did not evaluate the physical status of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…14 But no previous studies in Pakistan showed this association. 5,6,12 More studies are needed to confirm this trend of thrombocytosis in TB patients.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…3 The spread of this disease is caused by several factors notably Email: dryasmeenbatool@gmail.com the HIV/AIDS epidemic, low socio-economic status, overcrowding and malnutrition. [4][5][6] A study in Karachi provides evidence for a strong positive association between tuberculosis and diabetes. 7 A study in Jamshoro detected primary multi drug resistant tuberculosis more commonly in previously diagnosed and treated patients but also in newly diagnosed pulmonary patients and its due to dissemination of MDR cases within the community, difficult to treat.…”
Section: Introductionmentioning
confidence: 99%